Advance Technology in Application of Four Leg Inverters to UPQC - K. Venkata Rami Reddy; T. Gowri Manohar; B. Chandra Sekhar (Institute of Advanced Engineering and Science, 2016)
This article presents a novel application of four leg inverter with conventional Sinusoidal Pulse Width Modulation (SPWM) Scheme to Unified Power Quality Conditioner (UPQC). The Power Quality problem became burning issues since the starting of high voltage AC transmission system. Hence, in this article it has been discussed to mitigate the PQ issues in high voltage AC systems through a three phase Unified Power Quality Conditioner (UPQC) under various conditions, such as harmonic mitigation scheme, non linear loads, sag and swell conditions as well. Also, it proposes to control harmoincs with various artificial intelligent techniques. Thus application of these control technique such as Artifical Neural Networks, Fuzzy Logic makes the system performance in par with the standards and also compared with existing system. The simulation results based on MATLAB/SIMULINKTM are discussed in detail to support the concept developed in the paper.